O lúdico na formação de uma professora do começo da carreira até a PARFOR - MELO, Aldenice de Jesus dos Santos de (2023)
The objective of this work is to present the experiences from childhood to formation that will be presented in memorial form (1989 to 2023). In this sense, the construction of the memorial will present the aspects of life trajectory difficulties, struggles and victories until the entry into parfor to study pedagogy. Methodology will present Reflection on learning during the elaboration of the training memorial allows the process of narrating and listening to oneself and the Other to be a factor in the search for new professional identities and new knowledge. Thus, the memorial is a pedagogical device of critical reflection that reinvents the care of the person with himself and the care for the Other, a fact that is extremely relevant for the future professional gives education.